Islam, Islamism, and Post‐Islamism: Rediscovering Politics after the War on Terror. (March 2014) - Crowder, George; Griffiths, Martin; Hasan, Mubashar
<x xml:space="preserve">Abstract</x> Over the past twenty years, an influential body of conservative scholarship has focused on the alleged conflict between Islam and the West. Following widespread criticism of this scholarship, a number of commentators have revived its core assumptions to claim that the real conflict is between liberal democracy within Muslim societies and the political ideology of Islamism. In this article we trace the evolution of this scholarship, and suggest that recent empirical developments in the Muslim world suggest the potential for post‐Islamist parties to successfully adapt to the demands of democratic competition within Muslim societies. In this context, the emerging conflict is not between Islam and the West, or Islamism and the West, but between two very different discursive practices within the Muslim world that invoke Islam for radically different purposes. A traveler enters the world into which he travels, but a tourist brings his own world with him and never sees the one he's in.1